Development of a Bioanode for Microbial Fuel Cells Based on the Combination of a MWCNT‐Au‐Pt Hybrid Nanomaterial, an Osmium Redox Polymer and Gluconobacter oxydans DSM 2343 Cells. Issue 36 (22nd December 2017) - Aslan, Sema; Ó Conghaile, Peter; Leech, Dónal; Gorton, Lo; Timur, Suna; Anik, Ulku
Abstract: In this work, a carbon felt electrode (CFE) was modified with a multiwalled carbon nanotube‐gold‐platinum (MWCNT−Au‐Pt) hybrid nanomaterial and integrated with an osmium redox polymer (OsRP, [Os(2,  2'‐bipyridine)2 (poly‐vinylimidazole)10 Cl]Cl) and Gluconobacter oxydans DSM 2343 (G. oxydans) cells. The developed electrode was used as the bioanode in a 5.0 mM K3 Fe(CN)6 mediator containing phosphate buffer (pH 6.5) anolyte and combined with a Pt wire cathode in phosphoric acid medium (pH 3.5). As a result, a two chamber microbial fuel cell (MFC) was formed, in which an activated Nafion membrane was used as a proton exchange membrane. The OsRP/ G.oxydans /MWCNT−Au‐Pt/CFE based bioanode was electrochemically examined in differently deoxygenated bioanode chambers and additionally the amounts of hybrid nanomaterial and OsRP were optimized. In terms of MFC characteristics, it was found that an anaerobic OsRP/ G.oxydans /MWCNT−Au‐Pt/CFE bioanode based MFC had a maximum power density of 32.1 mW m −2 (at 90 mV), a maximum current density of 1032 mA m −2 and a charge transfer efficiency (E%) value of 22.30 (open circuit potential 180 mV). Abstract : An OsRP/ G.oxydans /MWCNT‐Au‐Pt/CFE based bioanode using two chamber microbial fuel cell (MFC) was formed, in which an activated Nafion membrane was used as proton exchange membrane. Developed bioanode was electrochemically examined in differently deoxygenated bioanode chambers and additionally the amounts of hybrid nanomaterial and OsRP were optimized. Finally, it was found that anaerobic OsRP/ G.oxydans /MWCNT‐Au‐Pt/CFE bioanode based MFC provided the maximum power and current density values, charge transfer efficiency and open circuit potential values among all trials.